Vietnam in Iraq: Tactics, Lessons, Legacies and Ghosts, 1st edition - Ryan, David, editor (Routledge, 2020)
More than most post-1970 conflicts involving US forces, the conflict in Iraq has been fought out against a background of frequently invoked memories from the era of the Vietnam War. The essays in this book offer a series of perspectives on connections and parallels between the Vietnam War and the 2003 invasion of, and conflict in, Iraq.